Clinical and Laboratory Characteristics of Children with Juvenil Idiopathic Arthritis: Single-Center Experience (Annals of Medical Research, 2021)
None
Keywords: Juvenile Idiopathic Arthritis; International League of Associations for Rheumatology; Children.